Central Asian regionalism and the roles of Russia and China: money, transport, energy, ideas - Krasnopolsky, Peter (2019)
International Relations studies of Central Asia tend to revolve around institutions, economics, security or socialization processes. However, due to the uncertain roles of competing regional institutions like the Eurasian Economic Union championed by Russia and the Shanghai Cooperation Organization and the Belt and Road Initiative championed by China, cooperation among Central Asian states is heavily dependent on the nature of engagement of the two major powers in the region, Russia and China. This thesis evaluates Central Asian regionalism by analyzing the impact placed by Russia and China on physical infrastructure. The findings suggest that the roles of the two countries have become increasingly interchangeable with Russia’s situational engagement having a limited or even negative effect on regional cohesion and China’s involvement visibly reshaping the region toward greater regional interconnectedness, but in different form. Multiple case studies of various projects in the networked sectors of infrastructure, i.e. transportation, energy and telecommunications, are used to build the argument and demonstrate the ways in which Russia’s and China’s engagement influence regional connectivity. The two major powers have had difficulty reaching a consensus about the format of multilateral lenders essential for the development of regional infrastructure, and therefore China-led financial institutions have become the major source of financing of infrastructural projects in Central Asia. The two powers’ engagement in the transportation sector partially decreased interdependence among Central Asian states, but Chinese projects aim to reconnect the region, particularly by linking Central Asia with South Asia. The shift toward interchangeability of the roles of Russia and China is most evident in the energy sector, which is characterized by Russia’s opportunism and China’s steps toward multilateral cooperation. In the telecommunication sector, the two major powers made limited impact on regional connectivity; however China’s use of material capabilities to affect information flows is gradually positioning the rising power as an important opinion shaper in the region. The study concludes that China’s capacity to build physical infrastructure and facilitate multiple multilateral initiatives with Central Asian states is slowly redirecting the region away from its historical dependency on Russia. Material capabilities, however, are not sufficient for regionalization, and it remains to be seen whether China is able to utilize its economic might to connect the region through shared ideas rather than just roads, pipelines, power lines and telecom cables.